Site-directed RNA editing by harnessing ADARs: advances and challenges - Ming Li; Cheng Yan; Yue Jiao; Yuqin Xu; Chen Bai; Rui Miao; Jiying Jiang; Jiao Liu (Functional & Integrative Genomics, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Proteomic analysis of coarse and fine skin tissues of Liaoning cashmere goat - Zhixian Bai; Yanan Xu; Ming Gu; Weidong Cai; Yu Zhang; Yuting Qin; Rui Chen; Yinggang Sun; Yanzhi Wu; Zeying Wang (Functional & Integrative Genomics, 2022)

Assessing trophic interactions among three tuna species in the Solomon Islands based on stomach contents and stable isotopes - Ri Jin Jiang; Fan Yang; Feng Chen; Rui Yin; Ming Zhi Liu; Wen Bin Zhu; Ai Guo; Lian Wei Liu (Frontiers in Marine Science, 2022)
Trophic research is essential to the conservation and management of fishery resources. This study analyzed the feeding habits and nutritional interactions among three tuna species in the waters of the Solomon Islands (5°12′S–15°20′S, 157°31′E–172°19′E). A total of 103 bigeye tuna ( Thunnus obesus ), 296 yellowfin tuna ( Thunnus albacores ), and 264 albacore tuna ( Thunnus alalunga ) samples were collected from September to December 2019. Samples for stomach content and stable isotope analysis were randomly selected. The stomach content analysis results showed that the stomach contents of the three tuna species were rich in prey, and 48 prey species were identified, including fish, cephalopods, and crustaceans, with high between-phenotype component (BPC). Yellowfin tuna consumed the largest variety of food and bigeye tuna consumed the smallest. The feeding intensity of bigeye tuna were higher than that of yellowfin and albacore tuna. Yellowfin tuna had the highest empty stomach rate (35.69%) and lowest average stomach fullness index (0.064). The degree of stomach fullness in the three tuna species was mainly 1, and the difference in the stomach fullness index among them was significant ( P <0.001). Food overlap (0.3–0.6) and Levins index (<0.6) among the three species were low, indicating a specialized feeding tendency. Bigeye tuna mainly feed on Ommastrephes bartrami and Myctophidae, yellowfin tuna mainly feed on Hyperiidea and Aluterus monoceros , and albacore tuna mainly feed on Gempylus serpens and Loligo chinensis . The stable isotope results showed that the δ 13 C and δ 15 N values of the three tuna species were significant ( P <0.001). The standard ellipse area corrected for small sample sizes (SEAc) and total niche area (TA) of bigeye tuna, range of δ 15 N (NR) of yellowfin tuna, and range of δ 13 C (CR) of albacore tuna were the highest. The results of this study will help improve our understanding of the feeding ecology of these three tuna species and their important roles in the ecosystem and food web structure.

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Spatiotemporal evolution of chlorophyll-a concentration from MODIS data inversion in the middle and lower reaches of the Hanjiang River, China - Zhuo Chen; Ming Dou; Rui Xia; Guiqiu Li; Lisha Shen (Environmental Science and Pollution Research, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

Microseismic signal denoising by combining variational mode decomposition with permutation entropy - Zhang Xing-Li; Cao Lian-Yue; Chen Yan; Jia Rui-Sheng; Lu Xin-Ming (Applied Geophysics, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)